Abdominal pain post bariatric procedure: What is the cause? Post bariatric abdominal pain - Tessier, Lea; Meyer, Daniel; Heath, Emily; Choi, Kyoo-Yoon (Journal of Surgery and Medicine, 2025)
Omental ischemia after bariatric surgery is a rare cause of abdominal pain. We report a case of a 42-year-old female with a history of Roux-en-Y gastric bypass (RYGB) presenting with abdominal pain. Despite biochemical, radiologic, and endoscopic investigation, no cause was identified. Ultimately, diagnostic laparoscopy revealed ischemic omentum. Post-operatively, her symptoms resolved. This case highlights the diagnostic challenges in patients post-RYGB presenting with abdominal pain with no clear cause. Division of the omentum is common practice during RYGB in the case of an antecolic Roux limb. This may predispose patients to omental infarction and ischemia, and as such, suspicion should be high when initial investigations are equivocal. The potential role of omental division during RYGB warrants further investigation. Furthermore, this case reinforces the importance of diagnostic laparoscopy in select cases. Rare causes of abdominal pain, such as omental ischemia, should be considered in patients who are post- RYGB. When initial investigations are negative, early diagnostic laparoscopy should be considered.